Vitamin D as a Possible COVID-19 Prevention Strategy - Bičíková, Marie; Máčová, Ludmila; Hill, Martin (International journal of molecular sciences, 2022)
Vitamin D is no longer considered an agent only affecting calcium phosphate metabolism. A number of studies over the past few years have demonstrated its role in immunomodulation and its influence on the development and functioning of the brain and nervous system. In the current epidemiological crisis caused by coronavirus disease 2019 (COVID-19), the immunoprotective role of vitamin D has been discussed by some authors regarding whether it contributes to protection against this serious disease or whether its use does not play a role. Non-standard approaches taken by laboratories in examining the serum levels of the vitamin D metabolite calcidiol have contributed to inconsistent results. We examined the serum of 60 volunteers in the spring and autumn of 2021 who declared whether they were taking vitamin D at the time of sampling. Furthermore, the tested participants noted whether they had experienced COVID-19. A newly developed liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was used to measure calcidiol levels. The analysis of variance (ANOVA) model of Statgraphics Centurion 18 statistical software from Statgraphics Technologies was used for calculations. The results of this study showed that those who took vitamin D suffered significantly less often from COVID-19 than those who did not take vitamin D.
Keywords: tandemová hmotnostní spektrometrie; COVID-19; Chromatography, Liquid; Humans; chromatografie kapalinová; Tandem Mass Spectrometry; lidé; vitamin D; Calcifediol; Vitamins; vitaminy; Vitamin D; LC-MS/MS determination; kalcifediol